Pengaruh Pelaksanaan Tank Cleaning dan Kemampuan Kru Terhadap Proses Efisiensi Bongkar Muat di Kapal MT. Pancaran 120 - Sultan; Eni Tri Wahyuni; Aan Rubiyanto (JURNAL BARTEK, 2025)
This research aims to analyze the influence of tank cleaning implementation and crew capabilities on loading and unloading efficiency on MT ships. PANCARAN 120. The author uses a quantitative approach and uses descriptive research methods to present findings based on the data collected. Questionnaires were used as a data collection tool in this research, which involved 20 respondents from the MT crew. beam 120, The data obtained were analyzed using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests, simple correlation analysis, simple linear regression analysis, T test, F test and R square test with the help of the SPSS version 26 programming base. The results of the analysis show that proper implementation of tank cleaning and crew capability have a significant influence on loading and unloading efficiency. From the results of this research, it can be concluded that proper implementation of tank cleaning and increasing crew capabilities contribute positively to loading and unloading efficiency at MT Pancaran 120. This research is expected to provide recommendations for tank cleaning implementers and loading and unloading managers to improve the loading and unloading process at MT. radiance 120.